(untitled) (REVISTA NODO, 2010)
The article presents a cinematographic approach to urban violence in Colombia from the point of view of local feature films. Based on the country’s violence time periods, agreed by both historians and filmmaking critics, the author selected six pictures that deal with the issue of violence within urban settlements to present a variety of positions towards the matter, such as the so called bipartisan violence in cities and municipalities, urban marginality and the ever more presence of drug dealing in the society, examining them in terms of what theoreticians and reviewers have already acknowledged. As a conclusion, the author emphasizes on the lack of analysis by Colombian critics that either turn down the subject of violence in the search of a more “positive” cinematography overlooking a reality that involves a vast portion of the population, or limit their scrutiny to verifying that what is being portrayed in the movies is historically correct without getting into broader discussions, leading to the fact that most truly critical proposals are actually coming from foreign universities.